Rasionalitas Masyarakat dalam Swamedikasi Vitamin C selama Pandemi Covid-19 - Febrial Hikmah (Jurnal Sains Biomedis, 2025)
Background: Self-medication, both with herbs and chemical supplements, is people’s choice in dealing with the COVID-19 pandemic. Vitamin C is the most widely consumed supplement by the public on a self-medicated basis during the pandemic. Consumption of vitamin C as daily consumption must be an important concern of the community so that it becomes beneficial for the body. The aim of the study: This research was conducted to rationality of society in self-medication of vitamin C during the COVID-19 pandemic. Research method: This research is a descriptive study using a cross-sectional design. This research was conducted using a community self-medication rationality questionnaire for vitamin C, including the right indication, the right storage, the right dose, the right way of giving, the right time of administration and being aware of side effects. Result: Based on the 289 respondents in this study, it was illustrated that 90.3% of the respondents consumed vitamin C to increase their immune system and 67.1% of the respondents consumed vitamin C not only when they were sick. 76.1% of respondents knew the dose before consuming vitamin C, 86.5% of respondents consumed vitamin C <1000 mg/day, and 50.2% of respondents consumed vitamin C ≥1000 mg/week. As many as 88.2% of respondents consumed vitamin C after eating and 85.1% of respondents read the rules of consumption. As many as 68.9% of respondents read the side effects on the packaging, 85.8% of respondents did not experience side effects after consuming vitamin C, and 91.3% of respondents did not experience gastric irritation after consuming vitamin C. As many as 87.2% of respondents stored vitamin C at room temperature and 93.8% of respondents stored in a closed container. Conclusions: Public rationality in self-medication with vitamin C during the COVID-19 pandemic is a good category (82%).